2022
DOI: 10.1112/plms.12473
|View full text |Cite
|
Sign up to set email alerts
|

Heegaard Floer homology for manifolds with torus boundary: properties and examples

Abstract: This is a companion paper to earlier work of the authors (Preprint, arXiv:1604.03466, 2016, which interprets the Heegaard Floer homology for a manifold with torus boundary in terms of immersed curves in a punctured torus. We establish a variety of properties of this invariant, paying particular attention to its relation to knot Floer homology, the Thurston norm, and the Turaev torsion. We also give a geometric description of the gradings package from bordered Heegaard Floer homology and establish a symmetry un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…We remark that Hanselman, Rasmussen, and Watson proved [HRW17] something more general than Theorem 1.1 in the Heegaard-Floer setting. In particular, they showed that the Heegaard-Floer homology of any toroidal manifold (not necessarily coming from a splice of knots in homology sphere L-spaces) has dimension at least five (over Z/2Z).…”
Section: Corollary 13 ([Zen18]mentioning
confidence: 82%
See 1 more Smart Citation
“…We remark that Hanselman, Rasmussen, and Watson proved [HRW17] something more general than Theorem 1.1 in the Heegaard-Floer setting. In particular, they showed that the Heegaard-Floer homology of any toroidal manifold (not necessarily coming from a splice of knots in homology sphere L-spaces) has dimension at least five (over Z/2Z).…”
Section: Corollary 13 ([Zen18]mentioning
confidence: 82%
“…A Heegaard-Floer analogue of Theorem 1.1, with coefficients in Z/2Z rather than Q, was first established by Hedden and Levine in [HL16], and later generalized by Eftekhary [Eft15,Eft20] and then by Hanselman, Rasmussen, and Watson [HRW17]. Their approaches all used bordered Heegaard Floer homology or something similar.…”
Section: Introductionmentioning
confidence: 99%
“…Call a curve loop‐type (respectively, arc‐type ) if there exists a ÎŽ>0$\delta >0$ so that the curve is ÎŽ$\delta$‐loop‐type (respectively, ÎŽ$\delta$‐arc‐type). We remark that this terminology differs from the one in [40], where loop‐type curves are compact curves with the trivial local system.…”
Section: Preliminariesmentioning
confidence: 99%
“…In the torus boundary case, Hanselman, Rasmussen, and Watson interpreted the bordered Heegaard Floer type D structure invariant as an immersed curve trueHF̂(M)$\widehat{\mathit {HF}}(M)$ in a once‐punctured torus [40]: (M,∂M=T2)1em↩1emtrueCFD̂false(Mfalse)scriptAfalse(T2false)1em↩1emtrueHF̂(M)↬T2∖1pt.\begin{equation*} (M, \partial M=T^2) \quad \mapsto \quad \widehat{\mathit {CFD}}(M)^{\mathcal {A}(T^2)} \quad \mapsto \quad \widehat{\mathit {HF}}(M) \looparrowright T^2\setminus 1\text{pt}. \end{equation*}Immersed curves in this context may contain several components, and each component comes with a local system.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation